The American jewelry revolution 1940-1960 - Jerman-Melka, Julie, author (Colorado State University. Libraries, 1998)
This thesis explores the inspirations and passions which transform my ideas into physical forms. My thesis work is the integration of the visual, the tactile and my personal spiritual search through my experiences with nature. As an artist, it is important for me to represent a visual balance, combined with tactile qualities, to create a sense of movement. This is achieved by layering metals such as copper, sterling silver and brass. In combination with the traditional metalsmithing techniques of embossing, granulation, anticlasitic forming and raising, I create work which has life and takes the viewer on a visual journey. The visual balance and sense of movement is created with various openings that pierce the metal, and also by playing with space and the asymmetry of form. I combine shapes, which have been stretched and textured. Finally, the pieces are soldered together to create rushing, exciting movement. I combine my vision of distant shores, the eyes of aspen trees and my interest in visual illusions and texture to create my metal work.
For Art History Seminar AR 592.
April 30, 1998.
Keywords: studio jewelers; Modernist Jewelry Movement; jewelry as art; metalsmithing